Fluctuations in global oil prices and their impact on the Fluctuations of global oil prices and their impact on the economies of rentier countries (Iraq as a model) - Khalaf, Qasim; Faraj, Sakna (The Gulf Economist, 2025)
This research aims to analyze oil price fluctuations and their impact on growth in Iraqi economic indicators represented by the domestic product and total public budget revenues, especially due to the importance of these indicators in the country’s economy. The focus was on the period from 2004-2023, where objective data issued by official bodies such as the Iraqi Central Bank and international organizations. However, the descriptive analytical approach was adopted: collecting and analyzing data related to oil prices and variables of the Iraqi economy in order to analyze the relationship between oil prices and the variables investigated. The research concluded with conclusions, including that oil revenues in Iraq are at a high percentage of the gross domestic product and budget revenues, and oil revenues are affected by fluctuations in the price of oil globally. This matter may lead to a negative impact on the Iraqi economy. The research recommended that a development model be studied that is compatible with the economic capabilities with its various material and human elements. In order to reach an effective model in the medium term that pushes towards eliminating rentierism, and leads to strengthening other economic sectors to contribute well to advancing the Iraqi economy.